2017
DOI: 10.1007/s00122-017-3029-7
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and limitations of multiple-trait genomic prediction for Fusarium head blight severity in hybrid wheat (Triticum aestivum L.)

Abstract: Predictabilities for wheat hybrids less related to the estimation set were improved by shifting from single- to multiple-trait genomic prediction of Fusarium head blight severity. Breeding for improved Fusarium head blight resistance (FHBr) of wheat is a very laborious and expensive task. FHBr complexity is mainly due to its highly polygenic nature and because FHB severity (FHBs) is greatly influenced by the environment. Associated traits plant height and heading date may provide additional information related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 81 publications
9
74
0
Order By: Relevance
“…As discussed previously, PH can affect disease pressure (Buerstmayr et al, 2002;Mao et al, 2010;Buerstmayr and Buerstmayr, 2016;Schulthess et al, 2018). Correlations between PH and FHB traits were negative in both years of our study, which agrees with the literature (Mao et al, 2010;Yan et al, 2011;Buerstmayr and Buerstmayr, 2016).…”
Section: Phenotypic Characteristicssupporting
confidence: 93%
“…As discussed previously, PH can affect disease pressure (Buerstmayr et al, 2002;Mao et al, 2010;Buerstmayr and Buerstmayr, 2016;Schulthess et al, 2018). Correlations between PH and FHB traits were negative in both years of our study, which agrees with the literature (Mao et al, 2010;Yan et al, 2011;Buerstmayr and Buerstmayr, 2016).…”
Section: Phenotypic Characteristicssupporting
confidence: 93%
“…For example, Schulthess et al (2017) reported that multivariate analysis improves parameter estimates. Authors like Calus and Veerkamp (2011), Jia and Jannink (2012), Jiang et al (2015), Montesinos‐López et al (2016), He et al (2016) and Schulthess et al (2017) reported better prediction accuracy of multivariate analysis compared to univariate analysis. These authors also agree that the genetic correlation between traits is the basis for the benefit of multivariate analysis; that is, that the larger the degree of relatedness between traits, the greater the benefit of multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Heritability for single locations was estimated following the concept of genomic heritability to evaluate the quality of field trials. This was done by estimating the prediction abilities applying fivefold crossvalidation as outlined in detail elsewhere (Schulthess et al 2018).…”
Section: Analysis Of Phenotypic Datamentioning
confidence: 99%